Strengthening Menstrual Fiqh Literacy for IPPNU and IPNU Youth through the Risālatul Maḥīḍ Study in Purwoasri Tegaldlimo Banyuwangi - Ilham Nur Kholiq; sofi Faiqotul Hikmah (CENDEKIA: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to strengthen literacy in the jurisprudence of menstruation (fiqh al-haid) for IPPNU and IPNU youth through a study of Risālatul Maḥīḍ in Purwoasri Village, Tegaldlimo District, Banyuwangi Regency. This program is motivated by the low understanding of youth regarding menstruation jurisprudence and the persistent stigma and sense of taboo surrounding discussions on the issue. The service method was implemented through participatory mentoring, including textual study, focused group discussions, fiqh case simulations, and the development of simple literacy media. The results of the service indicate an improvement in the knowledge, attitudes, and religious practices of both female and male youth, particularly in understanding the concepts of menstruation, istihadhah (irregular bleeding), and their implications for worship. Furthermore, this activity fostered the development of a more open and empathetic culture of fiqh literacy within the NU student organization environment.